2021
DOI: 10.47067/ramss.v4i1.99
|View full text |Cite
|
Sign up to set email alerts
|

Going Green: Theory of Reasoned Action Application to Examine the Consumer Intention Through Mediating Role of Green Technology Beliefs

Abstract: Technology usage has increased enormously in recent decades by different organizations to meet the consumers' growing demands. Technology growth has contributed to high energy consumption and overutilization of natural resources, which caused environmental deterioration. The awareness of eco-efficiency and sustainable environment has accelerated worldwide. Industries in developed countries have implemented green technologies to meet their environmental objectives. Developing countries also follow the same foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A few studies have also employed regression, ANOVA and Chi-square method. GR-banking studies have used different supporting theories such as social responsible investment theory (Alshebami, 2021; Ibe-enwo et al, 2019; Igbudu et al, 2018; Rehman et al, 2021), UTAUT (Bouteraa et al, 2020; Iqbal et al, 2018; Nisha et al, 2020; Rifat et al, 2016), UTAUT2 (Singh & Sahu, 2021), technology acceptance model (Naruetharadhol et al, 2021; Nisha, 2020; Shrivastava et al, 2019), stakeholder theory (Nisha, 2020), attractiveness theory (Iqbal et al, 2021), perceived risk theory (Iqbal et al, 2021), theory of planned behaviour (Burhanudin et al, 2021; Taneja & Ali, 2021), theory of reasoned action (Gill et al, 2021), self-regulation theory (Burhanudin et al, 2021), corporate environmental ethics ideology (Bukhari et al, 2022) and legitimacy theory (Chen et al, 2022). A few studies on GR-banking did not refer to any theory and instead built their studies on previous literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have also employed regression, ANOVA and Chi-square method. GR-banking studies have used different supporting theories such as social responsible investment theory (Alshebami, 2021; Ibe-enwo et al, 2019; Igbudu et al, 2018; Rehman et al, 2021), UTAUT (Bouteraa et al, 2020; Iqbal et al, 2018; Nisha et al, 2020; Rifat et al, 2016), UTAUT2 (Singh & Sahu, 2021), technology acceptance model (Naruetharadhol et al, 2021; Nisha, 2020; Shrivastava et al, 2019), stakeholder theory (Nisha, 2020), attractiveness theory (Iqbal et al, 2021), perceived risk theory (Iqbal et al, 2021), theory of planned behaviour (Burhanudin et al, 2021; Taneja & Ali, 2021), theory of reasoned action (Gill et al, 2021), self-regulation theory (Burhanudin et al, 2021), corporate environmental ethics ideology (Bukhari et al, 2022) and legitimacy theory (Chen et al, 2022). A few studies on GR-banking did not refer to any theory and instead built their studies on previous literature.…”
Section: Resultsmentioning
confidence: 99%
“…For example, from the perspective of employees, the study suggested technological-, organizational- and environmental-related factors that have not been explored in earlier studies of GR-banking adoption. Earlier literature has mainly focused on performance expectancy (Singh & Sahu, 2021), effort expectancy (Shafique & Khan, 2020), social influence (Singh & Sahu, 2021), bank policies (Rehman et al, 2021), GR technology belief (Gill et al, 2021), central bank regulations (Shafique & Majeed, 2020), management commitment (Bukhari et al, 2022) and GR investment need (Phuong, 2020). Similarly, from the perspective of customers, this study recommends considering religiosity, moral norms, environmental knowledge and GR experience.…”
Section: Discussionmentioning
confidence: 99%
“…A. Gill, Ansari, & Tufail, 2021). They should be inspired and implement HR green practices, and green HR training and upgrading system is another vital pillar of green HR practices (V谩zquez-Brust et al, 2022).…”
Section: Green Human Resource Practices and Proactive Environmental M...mentioning
confidence: 99%
“…In addition, studies that extended the applicability of TRA-focused variables, such as environmental attitudes, knowledge, advertising and behaviors (e.g. Ekawati et al ., 2023; Elahi et al ., 2022; Han, 2021; Zafar et al ., 2021; Gill et al ., 2021; Khan et al ., 2020; Pouratashi and Zamani, 2021; Lin and Xu, 2021; Troudi and Bouyoucef, 2020), did not focus on airports or used the combination of the current research variables. The particular focus on NAC will help in extending TRA as previous studies focused on countries such as Iran (Yaghoubi Farani et al ., 2019), Ghana (Adu-Gyamfi et al ., 2023) and Indonesia (Ekawati et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%